Synergizing Islamic Religious Education and Scientific Learning in the 21st Century: A Systematic Review of Literature - Nasucha, Muhammad Raihan; Khozin, Khozin; Thoifah, I’anatut (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
In the 21st century, the evolution of educational methodologies has significantly transformed Islamic Religious Education (IRE). This era demands students to acquire diverse competencies essential for their future, positioning IRE as crucial in mitigating the adverse effects of rapidly advancing science. To successfully navigate 21st-century Islamic education, an integration of religious and scientific knowledge is imperative. This approach aims to provide students with a comprehensive understanding and foster good values to counteract immoral behaviors. This research focuses on evaluating integrated learning concepts in implementing the 4C Skills (Critical thinking, Communication, Collaboration, and Creativity) among students. A qualitative approach, specifically a systematic literature review, was employed. The review involved meticulous selection and screening based on predetermined inclusion and exclusion criteria. The findings reveal that integrating IRE and science can manifest in learning evaluations. Implementing an integrated learning concept in evaluations positively influences student learning activities, spanning cognitive, affective, and psychomotor aspects, aided by the incorporation of 4C Skills in 21st-century learning environments.